A novel PAX3 mutation in a Chinese Han family with Waardenburg syndrome type 1. (August 2021) - Guo, Min; Li, Qing; Jiang, Chaowu; Li, Shuling; Ruan, Biao
Abstract: Objectives: To determine the clinical characteristics and genetic causes of Waardenburg syndrome type 1 (WS1) present in a Chinese Han family. Methods: Evaluations, including the familial history, clinical features and audiological tests, were performed on the proband and her parents. Genetic analyses were conducted using targeted next-generation sequencing of 144 known deafness genes, and confirmed by Sanger sequencing. Bioinformatics analyses of the candidate variant were performed. Results: The proband suffered from moderate hearing loss of the right ear, and her mother suffered from profound congenital bilateral hearing loss. The proband exhibited a left blue iris. The calculated W index of the proband was 2.61, while her mother's W index was 2.12. The proband and her mother were diagnosed with WS1 according to the Waardenburg Syndrome Consortium criteria. A novel missense variant NM_181457.3: c.127G > T; p.(Gly43Cys) in exon 2 in Paired Box 3 ( PAX3) was identified in the proband and her mother, but this variant was not detected in the father and the controls. This variant was not reported in the HGMD, ClinVar, 1000G and ESP6500 databases. Conclusion: We identified a novel missense variant in exon 2 of PAX3 as the genetic cause of WS1 in this two-generation family, which broadened the genetic spectrum of WS1.